Dampak Media Sosial Terhadap Partisipasi Masyarakat Dalam Pemilu Pada Tahun 2024 - Dhira Rizkia Ramara; Ginda Surya Trilestari; Shella Putri Amalia; Resthy Nuraeni Safitr; Muhammad Faishal Rabbani Zahran; Supriyono Supriyono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to identify patterns of social media usage, evaluate the effectiveness of social media campaigns, and explore the role of social media in voter education. This research discusses the influence of social media on public participation in the 2024 elections in Indonesia. Social media has become one of the main tools in political communication, both for candidates, political parties, and voters. This study uses a mixed-methods approach with surveys of 500 respondents from various regions in Indonesia, complemented by content analysis of political campaigns on social media platforms such as Instagram, Facebook, and TikTok. The level of voter participation who are actively engaged in online political discussions is also proven to be higher compared to those who are less active on social media. The issues found in the field include: 1. What are the social media platforms most commonly used by the public in the context of elections? 2. How is social media used to educate voters about political issues, candidates, and the electoral process? 3. What are the main challenges faced in using social media for electoral participation? The research method used is the quantitative method. This method involves the collection of data that can be measured and statistically analyzed. The research results show that social media plays a significant role in increasing political awareness among the public, especially among young voters. However, the research also found that information disseminated through social media is often unverified, which can negatively influence public opinion.